Accuracy verification and evaluation of small baseline subset (SBAS) interferometric synthetic aperture radar (InSAR) for monitoring mining subsidence. Issue 1 (1st January 2021) - Tao, Qiuxiang; Wang, Fengyun; Guo, Zaijie; Hu, Leyin; Yang, Chen; Liu, Tongwen
ABSTRACT: This study investigated the role of the number of differentialinterferograms and coherent threshold values on the accuracy of SBAS InSAR (small baseline subset interferometric synthetic aperture radar) results for specific applications in Jiyang Coal. Fifty-eight imageswere utilized to form fourdifferential interferogram timeseries with different numbers of interferograms and coherence thresholds. The four SBAS InSAR-monitored results, mining information of 15 working faces, and levelling-monitored results of 260 levelling points werecompared.The greater number of differential interferograms and lower coherent threshold values could better reflect the spatial distribution and variation trend of mining subsidence and demonstrate the advantages of SBAS InSAR. However, an excessive number of differential interferograms and excessively low coherent threshold values would increase the data processingdifficulty and the differences between SBAS InSAR- and levelling-monitoredresults. Location, spatial distributionandscopeofSBAS InSAR-monitored mining subsidence were consistent with the mining progress of the working faces.The accuracy ofSBASInSAR-monitored subsidence values followed a certain spatio-temporal variation law. The variation trend of absolute differences between SBAS InSAR-and levelling-monitored subsidence values was similar to the shape of the levelling-monitoredsubsidence basin, which was helpful to study the correction method of SBAS InSAR-monitored results.